Compare the Most Frequently Used Models of Risk Management - Jenei, Tünde (International Journal of Engineering and Management Sciences, 2016)
The successful risk management is based on the company can recognize and treat the risks well and effectively. Nowadays there are several techniques for risk management. Each technique breaks the risk management steps on its own logic. In this article we compare four different risk management models, accordingly what are the similarities, and what are the differences between the four models.